Automatic E-Invoice Data Entry into The AIS System of Polish Local Government - Cyryl KOTYLA (Communications of International Proceedings, 2021)
Purpose: The study aims to preliminarily identify the key factors limiting the implementation of automatic entry of electronic accounting documents regarding public procurement into the AIS system of the local government unit under examination. Design/methodology/approach: The research is a qualitative descriptive study incorporating the case study method as the research approach. Findings: Throughout entire 2020, the entity surveyed did not receive any electronic invoices regarding public-procurement. The contractors preferred traditional paper invoices. The study has additionally led to a conclusion that the three most significant impediments, i.e. conservative, organizational, and legal limitations. Research limitations/implications: The study is preliminary in character and requires a supplementary quantitative study conducted on a much larger, randomly selected sample. Practical implications: The study allowed for preliminary determination of the types of factors obstructing the process of automatic entry of electronic accounting documents regarding public procurement into the AIS systems of local government units, which, in turn, enabled preliminary analysis of the problem and preparation of background for broader research in this field. Originality/value: The literature on the subject offers no studies addressing the current state of the AIS data entry automation resulting from the provisions on electronic invoicing in public procurement.
Keywords: e-document; e-invoicing; e-accounting; AIS.